The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/ecm.1217
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus metabolism of reef organisms with algal symbionts

Abstract: Phosphorus (P), an essential structural and functional component of all living organisms, is considered to be the ultimate limiting nutrient in marine ecosystems. To optimize its acquisition, marine species such as protozoa, sponges, foraminifera, clams, and reef corals, among others, have entered symbiotic relationships with algae, which recycle waste products of the animal host and transform dissolved inorganic nutrients into organic molecules, making them bioavailable to their host. Such associations provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 176 publications
(431 reference statements)
2
59
0
Order By: Relevance
“…() recently showed that the direct transfer of fixed N and heterotrophic ingestion of diazotrophs provides a non‐negligible and important N source for Symbiodinium . This uptake of additional N from N 2 fixation can explain the observed 40% increase in the N:P ratio in Symbiodinium cells in the current study, which are in general constant (Ferrier‐Pagès, Godinot, D'Angelo, Wiedenmann, & Grover, ). Further, the shift in algal symbiont nutrient stoichiometry suggests that excess N uptake released Symbiodinium from their N‐limited state, an important regulatory mechanism maintaining the coral–algae symbiosis (Falkowski et al., ).…”
Section: Discussionsupporting
confidence: 57%
“…() recently showed that the direct transfer of fixed N and heterotrophic ingestion of diazotrophs provides a non‐negligible and important N source for Symbiodinium . This uptake of additional N from N 2 fixation can explain the observed 40% increase in the N:P ratio in Symbiodinium cells in the current study, which are in general constant (Ferrier‐Pagès, Godinot, D'Angelo, Wiedenmann, & Grover, ). Further, the shift in algal symbiont nutrient stoichiometry suggests that excess N uptake released Symbiodinium from their N‐limited state, an important regulatory mechanism maintaining the coral–algae symbiosis (Falkowski et al., ).…”
Section: Discussionsupporting
confidence: 57%
“…A T was indeed the strongest predictor for both G net and G budget , alone explaining more than half of the variation in reef growth rates in the present study. Interestingly, our study also identifies PO 4 3− concentration, an essential macronutrient and important source of energy for primary producers and reef calcifiers (Ferrier-Pagès et al, 2016), to be a strong abiotic correlate of reef growth. While an overload of inorganic nutrients can be detrimental for the calcification process (Fabricius, 2005; Tambutté et al, 2011), our results show that in a highly oligotrophic reef system, such as the Red Sea, reef growth might be positively affected by seasonal increases in PO 4 3− levels.…”
Section: Discussionmentioning
confidence: 61%
“…, Ferrier‐Pages et al. ), but we still know relatively little about how these processes transcend to the ecosystem scale. To improve understanding of these processes at larger scales of organization, exhaustive knowledge of all the components that underpin a coral reef nutrient budget is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Human activities are altering the nutrient budgets of coral reefs worldwide, through myriad ways, but the mechanisms that underlie these interactions remain poorly understood (Szmant 2002). Recent research is improving understanding of coral-nutrient interactions at the organismlevel (Wiedenmann et al 2013, Ferrier-Pages et al 2016), but we still know relatively little about how these processes transcend to the ecosystem scale. To improve understanding of these processes at larger scales of organization, exhaustive knowledge of all the components that underpin a coral reef nutrient budget is needed.…”
Section: Discussionmentioning
confidence: 99%